Economy Running the Nation, Nature Paying the Price: An Islamic Perspective on Environmental Disasters in Sumatra - Al Berto, Muhammad; Ahmad, Ahmad; Ghozali, Muhammad Lathoif (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
This study examines the link between rising deforestation in Aceh, West Sumatra, and North Sumatra and the ecological vulnerability that intensified hydrometeorological disasters in late 2025. The purpose of this research is to analyze deforestation trends, assess their connection to the ecological disasters that occurred, and explore these phenomena through an Islamic perspective. The study employs a qualitative method using a library research design, drawing on scientific sources, official reports, and secondary data on forest-cover loss and disaster documentation. The findings indicate a consistent increase in deforestation from 2019 to 2024, while cumulative forest loss from 2001 to 2024 has reached approximately 3.3 million hectares, significantly weakening the ecological capacity of forests to maintain hydrological balance and soil stability. The Islamic analysis reveals that excessive exploitation contradicts the principles of amanah (trust), mīzān (balance), and the prohibitions against fasād (corruption) and isrāf (excessiveness), demonstrating that environmental destruction carries moral and spiritual dimensions. This study concludes that forest management in Sumatra requires an approach grounded not only in ecological and economic considerations but also in Islamic values that emphasize stewardship, moderation, and sustainability.